2023
DOI: 10.1093/micmic/ozad026
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Wound-Healing Effect of Chemical and Green Synthesized Chitosan Nanoparticles Using Lawsonia inermis Ethanolic Extract

Abstract: Wounds can be a result of surgery, an accident, or other factors. There is still a challenge to find effective topical wound-healing agents. This study aims to investigate the wound-healing activity of chemical and green synthesized chitosan nanoparticles (Ch-NPs) using Lawsonia inermis leaves extract. The nanoparticles were morphologically and chemically characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and high-resolution transmission electron microscopy (HRTEM). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Metwally et al ( 2022 ) reported that the green synthesis of ZnO-NPs via the methanolic extract of HLE exhibited outstanding wound-healing efficacy with an undetectable scar, compared to chemically manufactured ZnO-NPs. Additionally, it has been shown that green-synthesized chitosan nanoparticles (Ch-NPs) utilizing HLE increase wound surface area, healing duration, and wound contraction percentage (Metwally et al, 2023 ). Henna seed extract (HSE) and ultrasound vibrations were utilized to create a spherical and irregular mixture of silver and gold nanoparticles (Au–Ag BNPs), with particle sizes ranging from 15 to 35 nm (Akilandaeaswari and Muthu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metwally et al ( 2022 ) reported that the green synthesis of ZnO-NPs via the methanolic extract of HLE exhibited outstanding wound-healing efficacy with an undetectable scar, compared to chemically manufactured ZnO-NPs. Additionally, it has been shown that green-synthesized chitosan nanoparticles (Ch-NPs) utilizing HLE increase wound surface area, healing duration, and wound contraction percentage (Metwally et al, 2023 ). Henna seed extract (HSE) and ultrasound vibrations were utilized to create a spherical and irregular mixture of silver and gold nanoparticles (Au–Ag BNPs), with particle sizes ranging from 15 to 35 nm (Akilandaeaswari and Muthu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%